Emergence and rate of autism in fragile X syndrome across the first years of life. (October 2020) - Roberts, Jane E.; Bradshaw, Jessica; Will, Elizabeth; Hogan, Abigail L.; McQuillin, Samuel; Hills, Kimberly
Abstract: Prospective longitudinal studies of idiopathic autism spectrum disorder (ASD) have provided insights into early symptoms and predictors of ASD during infancy, well before ASD can be diagnosed at age 2–3 years. However, research on the emergence of ASD in disorders with a known genetic etiology, contextualized in a developmental framework, is currently lacking. Using a biobehavioral multimethod approach, we (a) determined the rate of ASD in N = 51 preschoolers with fragile X syndrome (FXS) using a clinical best estimate (CBE) procedure with differential diagnoses of comorbid psychiatric disorders and (b) investigated trajectories of ASD symptoms and physiological arousal across infancy as predictors of ASD in preschoolers with FXS. ASD was not diagnosed if intellectual ability or psychiatric disorders better accounted for the symptoms. Our results determined that 60.7% of preschoolers with FXS met the Diagnostic and Statistical Manual of Mental Disorders (fifth edition) (DSM-5) criteria for ASD using the CBE procedure. In addition, 92% of these preschoolers presented with developmental delay and 45.4% also met criteria for psychiatric disorders, either anxiety, ADHD, or both. ASD diagnoses in preschoolers with FXS were predicted by elevated scores on traditional ASD screeners in addition to elevated autonomic arousal and avoidant eye contact from infancy.